Customer Accounting Information Usage and Organizational Performance - Hamzah, Al‐Mawali; Yuserrie, Zainuddin; Noor Nasir, Kader Ali (Emerald Group Publishing Limited, 2012)
This paper aims to shed light on the consequences of customer accounting (CA) information usage for strategic purposes on organizational performance. This is an empirical study with data from 106 Jordanian services organizations. Quantitative data were obtained to investigate the relationship between CA information items and organizational performance in the context of Jordan. The results show that the level of CA information usage (customer profitability, lifetime customer profitability analysis and valuation of customers as assets) impacts on organizational performance. CA information usage leads to better organizational performance. Also, the findings demonstrate a different effect of CA information items on diverse dimensions of organizational performance. The findings will help academics and managers to achieve higher organizational performance.